Electrochemistry of the NaI-AlBr3 Molten Salt System: A Redox-Active, Low-Temperature Molten Salt Electrolyte. Issue 3 (11th March 2021) - Percival, Stephen J.; Lee, Rose Y.; Gross, Martha M.; Peretti, Amanda S.; Small, Leo J.; Spoerke, Erik D.
Abstract : NaI-AlBr3 is a very appealing low melting temperature (<100 °C), salt system for use as an electrochemically-active electrolyte. This system was investigated for its electrochemical and physical properties with focus to energy storage considerations. A simple phase diagram was generated; at >100 °C, lower NaI concentrations had two partially miscible liquid phases, while higher NaI concentrations had solid particles. Considering the fully molten regime, electrical conductivities were evaluated over 5–25 mol% NaI and 110 °C–140 °C. Conductivities of 6.8–38.9 mS cm −1 were observed, increasing with temperature and NaI concentration. Effective diffusion coefficients of the I − /I3 − redox species were found to decrease with both increasing NaI concentration and increasing applied potential. Regardless, oxidation current density at 3.6 V vs Na/Na + was observed to increase with increasing NaI concentration over 5–25 mol%. Finally, the critical interface between the molten salt electrolyte and electrode materials was found to significantly affect reaction kinetics. When carbon was used instead of tungsten, an adsorbed species, most likely I2, blocked surface sites and significantly decreased current densities at high potentials. This study shows the NaI-AlBr3 system offers an attractive, low-temperature molten salt electrolyte that could be useful to many applied systems, though composition and electrode material must be considered.